2018
DOI: 10.1017/s0021932018000068
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Empowerment and Intimate Partner Violence in Bangladesh: Investigating the Complex Relationship

Abstract: The aim of this study was to assess whether women's empowerment ensures reduced intimate partner violence (IPV). The differential relationship between women's empowerment and IPV among married women in Bangladesh was investigated using 2007 Demographic and Health Survey data. Logistic regression models were used to assess whether women's empowerment had any influence on their likelihood of experiencing IPV while controlling for other covariates. The analyses revealed that older cohorts of women, who were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…24-26 A study in Bangladesh reported that women from the older age group were more likely to suffer from physical abuse by their husbands and partners. 27…”
Section: Discussionmentioning
confidence: 99%
“…24-26 A study in Bangladesh reported that women from the older age group were more likely to suffer from physical abuse by their husbands and partners. 27…”
Section: Discussionmentioning
confidence: 99%
“…However, the likelihood of domestic violence actually increased with consanguinity, once selection into consanguinity was corrected for in the IV model. It should be noted that consanguinity is a factor that is not yet incorporated regularly into analyses of marital quality (Sanawar et al, 2018). Next, the analysis explored the socioeconomic benefits of consanguineous marriage.…”
Section: Social and Economic Impacts Of Consanguinitymentioning
confidence: 99%
“…Women empowerment was measured in four dimensions, namely: 1) mobility, 2) decision-making power, 3) employment status and 4) headship of the respondent in the household. Mobility had two categories: 1. ability to go the medical/health center and 2. ability to go outside the house [6]…”
Section: Women Empowermentmentioning
confidence: 99%
“…In Bangladesh 85% of the workers in the garments sector are women and the development of the garment industry had a positive impact on female labor force participation as well as female years of schooling, which in turn delayed childbearing and female marriage in the urban areas in Bangladesh [20], [22]. The quick keenness of microcredit plans in rural areas of Bangladesh is often cited as a key to improving women"s empowerment by improving the authoritative power of women within households [6], [23]. The Union Parishad law 1997 encourages women participation in decision-making and empowerment process in Bangladesh and government instructed that women members should be president of at least twenty-five percent of these standing committees [2].…”
Section: Women Empowerment In Bangladeshmentioning
confidence: 99%
See 1 more Smart Citation